STUDENT PERSPECTIVES ON FINANCIAL LITERACY TO SUPPORT ENTREPRENEURIAL CHARACTER - Ahmad Nur Budi Utama; Agus Syarif (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
This article explains students' views on financial literacy to support students' entrepreneurial character. The campus environment plays a role in supporting student entrepreneurial activities. The development of the times followed by increasingly rapid technological developments makes the needs increase and then also has an impact on financial conditions. To respond to this from the beginning, students need knowledge about financial literacy. This study uses qualitative research methods based on data it is known that the level of financial literacy of students is at the level of sufficient literate (25%) and less literate (75%). Then the financial literacy aspect of students is quite good in terms of knowledge and savings, but students do not understand the importance of insurance and investment. It is very important to conduct financial literacy education so that students can understand good financial management to support student entrepreneurial potential. It is expected that educators also play a role in developing students' financial literacy so that these students can apply financial literacy well. Keywords: Entrepreneurship, Entrepreneurial Character, Finance, Financial Literacy, Student Perspective